A randomized controlled trial of empathetic refutational learning with health care professionals - Holford, Dawn; Mäki, Karl O.; Karlsson, Linda C.; Lewandowsky, Stephan; Gould, Virginia C.; Soveri, Anna (BMC, 2025)
Background Health care professionals are in a key position to promote vaccinations. However, consulting vaccine-hesitant patients can be difficult, especially when patients bring up anti-vaccination arguments. Whereas prior research has identified essential skills for refuting anti-vaccination arguments, little is known about how to acquire these skills. Our aim was to determine if empathetic refutational interview text scenarios help health care professionals build confidence and abilities in countering anti-vaccination arguments.
Methods We conducted an online randomized controlled experiment with UK and Finnish health care professionals in which we randomly assigned them to an empathetic refutational interview group (n = 167) or a control group (n = 180). Participants in the empathetic refutational interview group were presented with examples of the empathetic refutational interview approach, which encompasses the identification of attitude roots, affirmations, corrections of misconceptions, and provision of facts. Control group participants received a standard facts-based approach. We examined posttest use of empathetic refutational interview techniques and pre- and posttest perceived difficulty of refuting anti-vaccination arguments.
Results Participants in the empathetic refutational interview group used more empathetic affirmations than control group participants. The empathetic refutational interview group and the control group did not differ significantly in how often they explicitly tried to identify attitude roots, correct misconceptions, and provide vaccination facts, nor in how difficult they found anti-vaccination arguments to be to refute.
Conclusions Brief empathetic refutational interview text scenarios can increase health care professionals' use of affirmations when discussing vaccines with patients. Additional materials are needed to efficiently teach refutations of attitude roots.